2017
DOI: 10.4314/ijbcs.v11i2.3
|View full text |Cite
|
Sign up to set email alerts
|

Typologie des élevages de cobayes (<i>Cavia porcellus</i>) au Bénin

Abstract: , Tél: +229 97730503 RESUME Au Bénin, la caviaculture est méconnue du grand public. Elle est ignorée des chercheurs et des décideurs politiques. Ainsi, l'objectif de cette étude est d'identifier les zones d'élevage de cobayes, décrire les différentes techniques d'élevage et faire la typologie de ces élevages. A cet effet, une enquête conduite suivant la méthode en boule de neige a été utilisée. Il ressort de cette étude que l'élevage des cobayes se rencontre aussi bien en zone urbaine que rurale dans certaines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 7 publications
1
2
0
2
Order By: Relevance
“…Our analysis shows that the predominant species in the composition of diets corresponded to grasses (Poaceae), local forage resources (Asteraceae), tree resources, legumes (Leguminoseae) and kitchen waste. These results agree with a review article developed by Simtowe et al (2017) in sub-Saharan African countries (Côte d'Ivoire, Benin, Cameroon, Gabon, Democratic Republic of Congo, and Tanzania) in which the authors reported that the predominant C. porcellus (Ayagirwe et al, 2018;Faihun et al, 2017;Franklin et al, 2017;Kampemba et al, 2017;Kouadio Kouakou et al, 2015;Ngoula et al, 2017;Ngoupayou et al, 1995;Simtowe et al, 2017).…”
Section: Prospects Of Animal Feeding Practices and Technologysupporting
confidence: 89%
See 1 more Smart Citation
“…Our analysis shows that the predominant species in the composition of diets corresponded to grasses (Poaceae), local forage resources (Asteraceae), tree resources, legumes (Leguminoseae) and kitchen waste. These results agree with a review article developed by Simtowe et al (2017) in sub-Saharan African countries (Côte d'Ivoire, Benin, Cameroon, Gabon, Democratic Republic of Congo, and Tanzania) in which the authors reported that the predominant C. porcellus (Ayagirwe et al, 2018;Faihun et al, 2017;Franklin et al, 2017;Kampemba et al, 2017;Kouadio Kouakou et al, 2015;Ngoula et al, 2017;Ngoupayou et al, 1995;Simtowe et al, 2017).…”
Section: Prospects Of Animal Feeding Practices and Technologysupporting
confidence: 89%
“…Illiteracy levels in producers of C. porcellus reported for Sub-Saharan Africa were 55% (Benin), 19% (Côte d'Ivoire), 29% (Cameroon) and 42% (Democratic Republic of Congo) (Faihun et al, 2017;Herman et al, 2014;Mass et al, 2016). These were considered high and constitute an obstacle to improved production (Ayagirwe et al, 2018).…”
Section: Prospects Of Animal Feeding Practices and Technologymentioning
confidence: 99%
“…Les élevages caviacoles béninoises constituent une source de protéines surtout aux populations rurales des départements du Mono et du Couffo (situés au Sud-Est) mais également d'animaux de sacrifices dans les cultes de religions endogènes (Faihun et al, 2017). Au Bénin et à l'instar des autres pays africains, les cobayes reçoivent une alimentation inadéquate qui reste un handicap majeur au développement de ce type d'élevage (Niba et al, 2012 ;Faihun et al, 2017). En effet, dans la plupart des élevages caviacoles la ration quotidienne des animaux est souvent composée d'espèces graminéennes telles que Panicum maximum et Pennisetum purpureum (Noumbissi et al, 2014 ;Kouakou et al, 2010).…”
Section: Introductionunclassified
“…Their meat contains low fat, and more protein and minerals as compared to meat of other livestock species (Kouakou et al, 2013). They get mature earlier and they are prolific (Dikko et al, 2009;Lammers et al, 2009) with less competition to human as their diet is mainly made up of crop residues, kitchen wastes and forages (Bacigale et al, 2014;Kouakou et al, 2015 andFaihun et al, 2017). They are easily reared with other species such as rabbits (Lammers et al, 2009), and they require less care if kept in relatively clean environment (NRC, 1991;Lammers et al, 2009).…”
Section: Introductionmentioning
confidence: 99%